PROFESSORES DOS ANOS INICIAIS DO ENSINO FUNDAMENTAL E SUAS IDEIAS SOBRE HISTÓRIA E ENSINO DE HISTÓRIA - Telles, Michele Rotta (2015)
The object of the research are the ideas about history and History teaching by single-teachers of Early Years (fifth year) of the Elementary School of Municipal schools of Ponta Grossa, Paraná. Therefore, the guiding questions relate to how teachers understand history and how they conceive the discipline of history; how they relate to historical knowledge and school knowledge; and what is the relationship between their personal/ professional identities and the characteristics of understanding history teaching in the Elementary School. The research is based on discussions about History teaching, mainly in the theoretical construct of Jörn Rüsen because the processes of constitution and operation of historical consciousness of teachers are considered, is the basic intellectual processes of historical thinking. It is also employed the theory of social representations of Serge Moscovici, as the historical consciousness of teachers also comprises representations that build on history and history teaching throughout their personal and professional trajectories. Discussions about school knowledge of Jean Claude and Yves Forquin Chevallard are still undertaken, given that the relations established by teachers with historical knowledge and history teaching influence and are influenced in the gears of historical consciousness. The objective of the research is to identify and understand the representations of teachers of Elementary School about the history and History teaching, considering the formation of modes of historical consciousness, and understandings about school knowledge. Therefore, we applied a questionnaire to teachers of classes of fifth year of the Municipal council of Education, whose data were treated by the software EVOC 2000 and PSPP. Then there were produced graphs and charts about teachers‟ personal/professional profiles, the evocations of words about the meaning of history, and the classification used in defining what is history and the objectives of teaching it. Data analysis combined the methodological procedures related to the research on social representations, especially the theory of the central nucleus of the representations, Jean Claude Abric, with explanations of Jörn Rüsen to the sense constitution modes of historical consciousness. It was found that the meanings of teachers about the history and History teaching in Elementary School tend to vary according to teacher‟s education, and relate in different ways to the historical knowledge and school knowledge. Research results have collaborated to unveil theoretical and methodological gaps in teacher training; contextualize curricular barriers and pedagogical barriers of Municipal Education; and relate the teachers‟ personal and professional biographies and, understanding that single-teachers think teaching and History in Years EF Initials from mostly rooted understandings both in school enrollment as in the curricula of their respective formation.